Genetic diversity in an African plantain core collection using AFLP and RAPD markers - Ude, G.; Pillay, M.; Ogundiwin, E.; Tenkouano, A. (Springer, 2003)
Fifteen AFLP primer pairs (EcoRI+3 and MseI+3) and 60 10-mer RAPD primers were used to detect polymorphisms and assess genetic relationships in a sample of 25 plantains from diverse parts of Western and Central Africa. The discriminatory power of the AFLP technique was greater than that of the RAPD technique, since the former produced markers with greater polymorphic information content (PIC) than the latter. Hence, AFLP analysis appeared to be a more-powerful approach for identifying genetic differences among plantain accessions. In this regard, significant genetic diversity within the plantains was shown by the unweighted pair-group method of arithmetic averages (UPGMA) and the multidimensional principal coordinate (PCO) analyses. The AFLP-derived clusters indicated closer relationships between similar inflorescence types than the RAPD-derived clusters. A small group of cultivars from Cameroon were separated from the bulk of other plantains, suggesting that Cameroon may harbour accessions with useful or rare genes for widening the genetic base of breeding populations derived from the plantains. A greater effort should be directed at collecting and characterizing plantain cultivars from Cameroon.